Probiotics: an update - Yvan Vandenplas; Geert Huys; Georges Daube (Elsevier, 2015)
OBJECTIVE: Triggered by the growing knowledge on the link between the intestinal microbiome and human health, the interest in probiotics is ever increasing. The authors aimed to review the recent literature on probiotics, from definitions to clinical benefits, with emphasis on children. SOURCES: Relevant literature from searches of PubMed, CINAHL, and recent consensus statements were reviewed. SUMMARY OF THE FINDINGS: While a balanced microbiome is related to health, an imbalanced microbiome or dysbiosis is related to many health problems both within the gastro-intestinal tract, such as diarrhea and inflammatory bowel disease, and outside the gastro-intestinal tract such as obesity and allergy. In this context, a strict regulation of probiotics with health claims is urgent, because the vast majority of these products are commercialized as food (supplements), claiming health benefits that are often not substantiated with clinically relevant evidence. The major indications of probiotics are in the area of the prevention and treatment of gastro-intestinal related disorders, but more data has become available on extra-intestinal indications. At least two published randomized controlled trials with the commercialized probiotic product in the claimed indication are a minimal condition before a claim can be sustained. Today, Lactobacillus rhamnosus GG and Saccharomyces boulardii are the best-studied strains. Although adverse effects have sporadically been reported, these probiotics can be considered as safe. CONCLUSIONS: Although regulation is improving, more stringent definitions are still required. Evidence of clinical benefit is accumulating, although still missing in many areas. Misuse and use of products that have not been validated constitute potential drawbacks.